Alien abductions - Karst, Ken (Mankato, MN : Creative Education, 2018)
"An investigative approach to the curious phenomena and mysterious circumstances surrounding alien abductions, from abductees' hypnotic recollections to conspiracy theories to hard facts"--
What was that? -- Fake news, 1938 -- A few explanations -- Who writes this stuff? -- The abduction Hall of Fame -- Who you gonna call? -- Plenty of questions -- Campaigning ETs.
Includes bibliographical references and index.
Keywords: Human-alien encounters -- Juvenile literature; Alien abduction -- Juvenile literature; Unidentified flying objects -- Sightings and encounters -- Juvenile literature